2010
DOI: 10.1073/pnas.1000526107
|View full text |Cite
|
Sign up to set email alerts
|

Roles of glutamates and metal ions in a rationally designed nitric oxide reductase based on myoglobin

Abstract: A structural and functional model of bacterial nitric oxide reductase (NOR) has been designed by introducing two glutamates (Glu) and three histidines (His) in sperm whale myoglobin. X-ray structural data indicate that the three His and one Glu (V68E) residues bind iron, mimicking the putative Fe B site in NOR, while the second Glu (I107E) interacts with a water molecule and forms a hydrogen bonding network in the designed protein. Unlike the first Glu (V68E), which lowered the heme reduction potential by ∼110… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
141
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(155 citation statements)
references
References 68 publications
13
141
1
Order By: Relevance
“…During the last few decades, swMb has been well studied as a represent heme protein. In addition, it has been widely used as a protein model for rational design of artificial heme proteins with novel functions [1,4,[8][9][10][11]. Comparatively, the structureactivity relationship has not been fully understood for the unique apMb [6,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 98%
“…During the last few decades, swMb has been well studied as a represent heme protein. In addition, it has been widely used as a protein model for rational design of artificial heme proteins with novel functions [1,4,[8][9][10][11]. Comparatively, the structureactivity relationship has not been fully understood for the unique apMb [6,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 98%
“…Besides inorganic model compounds [32] (and references therein), an engineered sperm whale myoglobin was constructed [33,34]. It successfully reproduced the NOR active centre with the magnetic coupling between the two iron sites, but experiments carried out in the presence of NO have shown low reductase activity [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…They also demonstrated that adding a second glutamic acid was critical. This Glu is seen in the native enzyme and increased reactivity by 100% in the artificial enzyme, which the authors ascribe to a hydrogen bond between the Glu and water-promoting proton transfer (199). Furthermore, they demonstrated that the metal at this site can both structurally and electrochemically tune the active site.…”
Section: Protein Redesignmentioning
confidence: 94%